'Urf Analysis on Electronic Money (E-Money) Use (Study Case: Lecturer of Economics and Islamic Business UIN North Sumatra Medan) - Nurul Jannah; Asmuni Asmuni; Tuti Anggraini (University of Darussalam Gontor, 2022)
Circulating government regulations regarding the use of e-money, people began to obey them by using e-money until finally the use of e-money has become a habit for the majority of Indonesian people. The basic law of muamalah in Islam is permissible until there is a proposition that prohibits it, so with this shift in habit, whether custom or in ushul fiqh science is called 'urf. This study aims to analyze 'urf on the use of electronic money (e-money) at the lecturers of the Islamic economics and business faculty of UIN North Sumatra Medan, this qualitative research uses the case study method. The researcher conducted observations on all permanent lecturers of the undergraduate program and of the sixty-two lecturers of the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra Medan, the researcher will conduct interviews only with ten representatives of lecturers of the Faculty of Economics and Islamic Business, State Islamic University of North Sumatera, Medan with criteria ranging from 25-40 years old and the lecturer understands about electronic money and has used electronic money (e-money) outside of campus mandatory transactions. This study results that the use of e-money is included in the 'urf sahih category, which means that the use of e-money is a habit that does not conflict with the arguments of the Qur'an and Hadith, the use of e-money also includes 'urf 'amm which means e-money known, known, agreed upon and applied by the majority of the community, the use of e-money also provides benefits to the community. So the use of e-money is an 'urf that can be used as the basis for legal determination